Deprotonation of large calixarenes-cation binding and conformations - Harrowfield, J.; Koutsantonis, G.; Ogden, Mark; Sobolev, A.; White, A. (CSIRO Publishing, 2016)
© 2016 CSIRO. Single crystal X-ray studies of p-t-butylcalix[10]arene·2dmso·7H2O (1) and [NMe4][p-t-butylcalix[9]arene-H]·2dmso·H2O (2), provide new data on these large macrocycles and their conformations, that of 2 being the first where an encapsulated [NMe4]+ cation is present, while 1 contains the neutral ligand. Both were obtained as crystalline products of the reactions of the calixarenes with tetramethylammonium hydroxide after prolonged standing. The structure of [NEt4][calix[4]arene-H], in which the cation approaches inclusion in the shallow cone of the anion, is also defined and compared with various other alkylammonium derivatives of calixarenes as well as that of p-t-butylcalix[9]arene.